Factors of IT Project Failure: A Literature Review - Betantiyo Prayatna; Muhamad Ihsan Suzeta; Honaris Clausa (Pt. Anagata Sembagi Education, 2025)
This study aims to identify the key factors contributing to IT project failure. A literature review serves as the primary research method, with articles sourced from leading journal databases such as Scopus, IEEE Xplore, Google Scholar, and ProQuest using the keyword